Women in the American Revolution - Wike, Sudie Doggett (McFarland & Company, Inc., Publishers, 2018)
"Without the support of American women, victory in the Revolutionary War would not have been possible. They followed the Continental Army, handling a range of jobs usually performed by men. The author focuses on the many key roles women filled in the struggle for independence, from farming to making saltpeter to spying"--